Control over the Hydrogen‐Bond Docking Site in Anisole by Ring Methylation. Issue 5 (23rd December 2015) - Gottschalk, Hannes C.; Altnöder, Jonas; Heger, Matthias; Suhm, Martin A.
Abstract: The supramolecular docking of methanol to anisole may occur via an OH⋅⋅⋅O hydrogen bond or via an OH⋅⋅⋅π contact. The subtle balance between these two structures can be varied in supersonic jets by one order of magnitude through single to triple methylation of the aromatic ring and introduction of a single tert ‐butyl substituent, as evidenced by infrared spectroscopy. This steep variation makes it possible to assess the accuracy of relative quantum‐chemical energy predictions on a kJ mol −1 level, promising insights into inductive, mesomeric, and dispersive effects. The zero‐point‐corrected B3LYP‐D3/aVTZ level is shown to provide an accurate relative description of the two very different hydrogen bonds, similar to a wavefunction‐based protocol including CCSD(T) corrections applied to the same structures. M06‐2X alone systematically overestimates the stability of π coordination. Abstract : π or O? It's all in the balance ! The alkylation pattern of anisole influences the preferred docking site for the OH group of a methanol solvent molecule—at the ether oxygen or the π system of the ring. Vibrational spectroscopy of molecular pairs at low temperature reveals the preferences of this intermolecular balance and provides kJ mol −1 quality ratings for quantum chemical predictions.